EFEKTIVITAS EKSTRAK DAUN SIRIH MERAH TERHADAP JUMLAH KOLONI BAKTERI PADA REMAJA PEREMPUAN YANG MENGALAMI KEPUTIHAN - Pascawati, Riana; Hidayanti, Desi (Poltekkes Kemenkes Bandung, 2024)
Leukorrhea, or vaginal discharge, is a common issue faced by adolescent girls during puberty. The Indonesian Adolescent Reproductive Health Survey reports that 31.8% of young women experience this condition, indicating their increased vulnerability to vaginal infections. Bacterial growth is a primary cause of leukorrhea, particularly in adolescent girls whose thin vaginal mucosa provides a favorable environment for bacterial proliferation, resulting in excessive fluid production and discomfort. Red betel leaf extract, containing natural antiseptics and antibiotics, offers an effective treatment for leukorrhea. The research sought to examine how extract from Piper crocatum (red betel leaf) impacts the growth of bacteria responsible for leukorrhea in young female adolescents. The research employed the Total Plate Count method to measure aerobic bacterial colony numbers in the participants' leukorrhea samples The research employed a quasi-experimental methodology, utilizing a single group pre-post test design and sequential sampling. Results demonstrated a notable impact of red betel leaf extract on the quantity of bacterial colonies in teenage girls. The statistical evaluation produced a p-value below 0.05 (specifically, 0.02), validating the extract's effectiveness. The research concludes that red betel leaf extract, a readily available natural remedy, can serve as an effective therapy to reduce bacterial colonies responsible for leukorrhea in adolescent girls. This herbal treatment's accessibility makes it a practical option for community use.